FAKTOR YANG BERHUBUNGAN DENGAN KEKAMBUHAN HIPERTENSI - Dharmawan, Rio Lucky; Nurarifah, Nurarifah; Utami, Utami; Palayukan Singkali, Dina; Wahyurianto, Yasin (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Hypertension is another name for high blood pressure, blood pressure is the strength of blood flow from the heart that drives the walls of blood vessels (arteries). Data from the World Health Organization (WHO) in 2015 showed that around 1.13 billion people worldwide suffer from hypertension. The number of people with hypertension in the world continues to increase in 2025 there will be 1.5 billion people affected by hypertension. It is estimated that every year 9.5 million people die from hypertension and complications every year. Factors that cause hypertension recurrence consist of factors that can not be changed such as age and sex and factors that can be changed such as medication adherence, salt consumption, smoking habits, obesity, lack of physical activity, stress and so on. The purpose of this study was to determine the factors associated with hypertension recurrence. The design of this study is cross sectional which is a research design in which data for independent and dependent variables are obtained at the same time and simultaneously, the number of samples is 45 respondents with total sampling technique. The results of the study with statistical tests indicate the value of taking medication adherence p value: 0,000, dietary patterns p value 0.001, and stress p value 0.011 where both are smaller than alpha (p <0.05). The conclusion is that there is a significant relationship between medication adherence, diet, and stress on hypertension recurrence. The recommendations of the results of this study are that respondents are more aware of the factors associated with hypertension recurrence by complying with medication, eating patterns, and avoiding stress.Keywords: Hypertension, Compliance with Medication, Diet, Stress